2016
DOI: 10.3109/00207454.2016.1148034
|View full text |Cite
|
Sign up to set email alerts
|

Development of stem cell-based therapies for Parkinson's disease

Abstract: I.Abstract Parkinson's disease (PD) is a common neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons of the substantia nigra pars compacta (SNpc) in the brain with an unknown cause. Current pharmacological treatments for PD are only symptomatic and there is still no cure for this disease nowadays. In fact, transplantation of human fetal ventral midbrain cells into PD brains have provided a proof of concept that cell replacement therapy can be used for some PD patients, benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 66 publications
(63 reference statements)
0
11
0
1
Order By: Relevance
“…Incomplete differentiation of ESC is a major challenge for the development of an effective PD therapy and the risk of tumorigenesis may prevent the applications of ESC [ 287 ]. Induced pluripotent stem cells (iPSCs) are better sources for PD as these can be derived from the patients, thus eliminating the risk of immune rejection and the requirement of immunosuppressive therapy [ 293 ]. Unlike ESCs, iPSCs are not hindered by ethical issues [ 294 ].…”
Section: Future Directions: Search For Biomarkers and Neuroprotectmentioning
confidence: 99%
“…Incomplete differentiation of ESC is a major challenge for the development of an effective PD therapy and the risk of tumorigenesis may prevent the applications of ESC [ 287 ]. Induced pluripotent stem cells (iPSCs) are better sources for PD as these can be derived from the patients, thus eliminating the risk of immune rejection and the requirement of immunosuppressive therapy [ 293 ]. Unlike ESCs, iPSCs are not hindered by ethical issues [ 294 ].…”
Section: Future Directions: Search For Biomarkers and Neuroprotectmentioning
confidence: 99%
“…A bunch of studies reported the generation of dopaminergic neurons from NSCs (Ding et al 2016;Lee et al 2016a, b). Due to the fact that degradation of dopaminergic neurons plays key roles in the pathology of Parkinson's disease (PD), development of stem cell-based therapy is one of the most promising way in the treatment of PD (Zhu et al 2016). PD is a disorder of the central nervous system that mainly affects the motor system (Keranen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to transplantation, three fundamental aspects must be addressed: the identification of a transplantable stage during DA neuron differentiation, in vivo DA neuronal survival, and functional assessment [10]. Currently, efficient DA neuron generation has been produced using FP-based methods [8,12,13,15,21,[29][30][31]. Different stages of DA cells have been examined individually in vivo and different conclusions have been reached [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%